Uncovering Multifaceted Iodonium Ylides: Versatile Reactivity Enables Cyclization of Simple Arylamines - Zhang, Liang; Wang, Yao (Synlett, 2018)
Iodonium ylides can undergo cyclization with a simple tertiary arylamine to afford N-heterocyclic products in a transition-metal-free approach in the absence of an additional initiator/oxidant. The inherent reactivity uncovered in this transformation is fundamentally different from known chemical properties of iodonium ylide compounds, thus providing a new opportunity for the further exploration of iodonium ylide-based chemical transformations. This Synpacts article describes the historical background of iodonium ylide chemistry and highlights recent progress disclosed by our work.1 Introduction2 The Strategy for New Reaction Discovery3 Application to Cyclization of Tertiary Arylamines4 Conclusion and Perspectives
Keywords: iodonium ylide; tertiary arylamine; cyclization; N-heterocycle; electron transfer